Pengembangan Sistem Konsultasi dan Pencarian Pengacara berbasis Website - Entin Endah Cahyati; Nurudin Santoso; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Law is rules in written or unwritten form, which are arraned into a system that determines what can and cannot be done by humans in social life. To protect an prevent misuses of the law, we need someone who understands the problem that exist whithin the scope of the law, namely lawyers. Before determining the suitability of our cases with a lawyer, a consultation is needed about the case we are facing. Today many people need lawyers but to get it is difficult, which one is the mismatch between lawyer and client. To find out whether a lawyer is suitable or not with a client, first the client must consult with the lawyer. To facilitate the search and consultation of lawyers, a system is provided that can be used to consult and search for lawyers. The process for developing this research is using the Rapid Application Development (RAD) method with an Object-Oriented (OO) approach and website-based. To find out whether a lawyer is suitable or not with a client, first the client must consult with the lawyer. To facilitate the search and consultation of lawyers, a system is provided that can be used to consult and search for lawyers. The process for developing this research is using the Rapid Application Development (RAD) method with an Object-Oriented (OO) approach and website-based.italic.